Pandangan Muhammad Shahrur Mengenai Konsep Pakaian Perempuan Muslim - Laili, Nurul Fithriyah Awaliatul; Aziz, Akbar Nur (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2023)
This research aims to analyze how Shahrur's interpretation of the Koran responds to the concept of Muslim women's clothing. This research uses a literature review method with a descriptive qualitative approach. Research data was obtained from national and international journals and reference books over the last 10 years. Data analysis is carried out by collecting data, describing it into units, carrying out synthesis, compiling patterns and making conclusions. The results of this research indicate that the traditional understanding of the hijab and women's clothing in Islam according to Shahrur has been misunderstood and practiced. Al-Quran verses that are often quoted to support Muslim women's obligation to wear the hijab, such as Surah An-Nur verse 31, are not intended to suppress or limit women, but rather to protect them from potential violence and sexual objectification in society at that time. Shahrur argues that traditional interpretations of these verses have ignored their social-historical context.